Optimization of methods of cleaning and inactivation of feline calicivirus activator of cats - Недосєков, В. В.; Козленко, Т. Г. (Scientific Progress & Innovations, 2016)
We found that the best method of obtaining a purified preparation of calicivirus is ammonium sulfate precipitation followed by purification of the antigenic material using gradient sucrose concentration, which enables to obtain purified preparation pathogen, suitable for the production of antigen. Comparative study modes formalin inactivation showed that optimal for virus inactivation is the effect of formalin in an amount of 0,2 % at 37 °C and 72 hours of exposure.